All Days 2013
DOI: 10.2118/164320-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Signal Analysis of an Electrical Submersible Pump Failure Due to Scaling

Abstract: The present paper is concerned with a study of electrical submersible pump failure due to scale build-up. From motor current signals recorded several weeks before the failure, weak fluctuations were recorded, indicating a change in the motor load. The advanced signal analysis of the motor current data revealed the presence of a dynamical character of the electrical submersible pump signal when scale started rapidly building up in the pump stages. Based on the raw data from the motor current draw a dynamical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Apart from energy savings, the DCR motor also reduces the production of greenhouse gases and push down the total environmental cost of electricity generation. M. N. NouiMehidi et al [6] revealed that the ESP system before failure exhibits a gradual evolution towards a chaotic behavior that can be clearly identified through the signal analysis of the recorded data from the motor current. These results open the door on the possibility of developing a new real time diagnostics tool that could predict the failure of the ESP system due to scale build -up and allo w better management of the production protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from energy savings, the DCR motor also reduces the production of greenhouse gases and push down the total environmental cost of electricity generation. M. N. NouiMehidi et al [6] revealed that the ESP system before failure exhibits a gradual evolution towards a chaotic behavior that can be clearly identified through the signal analysis of the recorded data from the motor current. These results open the door on the possibility of developing a new real time diagnostics tool that could predict the failure of the ESP system due to scale build -up and allo w better management of the production protocols.…”
Section: Introductionmentioning
confidence: 99%